Utilization of the Integrated Management of Newborn and Childhood Illness (IMNCI) protocol and associated factors among health care workers in health centers of South Gondar Zone, Northwest Ethiopia: an institution-based mixed study - Belete, Abraham Addis; Agumas, Yeshambel; Tsehay, Asmamaw Ketemaw; Ayele, Habtamu Molla (Frontiers in Health Services, 2024)
Introduction Globally, 11 million children have died before reaching their fifth birthday. The introduction of the Integrated Management of Newborn and Childhood Illness (IMNCI) protocol reduces the morbidity and mortality rates among children under the age of 5. However, the share of neonatal mortality is increasing. As a result, the United Nations has established sustainable development goals to reduce national neonatal death rates through the utilization of the Integrated Management of Newborn and Childhood Illness protocol as the main tool for 12 per 1,000 live births by 2030. However, the death rate from preventable causes has increased owing to the low utilization of the protocol. Objective The objective of this research is to assess the utilization of the IMNCI protocol and associated factors among healthcare workers (HCW) in health centers at the South Gondar Zone, Northwest Ethiopia, in 2022. Methods The institution-based mixed study design was conducted from November to December 2022 at the South Gondar Zone, Amhara. A total of 422 HCW were selected using a computer-generated random-number generator. Data were cleaned and entered into EpiData 3.1 software and analyzed using SPSS version 25.0. Binary logistic regression was used to identify candidates for multivariable logistic analysis with p-value < 0.2, and for multivariable analysis, p-value < 0.05, with a 95% confidence interval, was considered significant. Thematic analysis was used for the qualitative data. Results In total, 417 respondents were included in the final analysis. The overall response rate was 98.8%, and the mean age was 30.01 years. The results showed that the proportion of IMNCI utilization was 63.1%. The odds of the utilization of IMNCI protocol among HCW who took training were 3.13 times higher than those among HCW who did not take training [adjusted odds ratio (AOR) = 3.13, 95% CI: 1.594, 6.147]. The lack of drugs reduces the utilization of the IMNCI protocol by 75.7% compared with the use of drugs (AOR = 0.243, CI: 95%:0.128, 0.464). HCW who always referred to the chart booklet during case management were 3.34 times more likely to utilize the IMNCI protocol (AOR = 3.34, 95% CI: 1.99, 5.60) compared with those who did not refer to the chart booklet. Conclusions and recommendations The utilization of the IMNCI protocol was low. A shortage of medical consumables and equipment attitude and training were identified as factors that affected the utilization of the protocol. Therefore, the availability of necessary logistics and training for employees with regular supportive supervision and monitoring should be conducted with the integration of sectors at the district and zone levels.